Analysis of Mathematical Reasoning Ability Based on Introverted and Extroverted Personality Types Among Tadris Mathematics Undergraduate Students - Sheila Sutiawati; Ria Deswita (Supermat : Jurnal Pendidikan Matematika, 2025)
Mathematical reasoning ability is an essential aspect of mathematics education, especially for Tadris Mathematics students who are prepared as future educators. One internal factor that may influence this ability is personality type. Introverted and extroverted students differ in the way they process information and make decisions, which may lead to distinct characteristics in their reasoning abilities. This study aims to analyze the mathematical reasoning abilities of students in solving linear programming problems by considering introverted and extroverted personality types at the State Islamic Institute of Kerinci. This research employs a qualitative approach with a descriptive design. The subjects were selected using purposive sampling and consisted of four Tadris Mathematics students whose personality types had been identified through the Myers-Briggs Type Indicator (MBTI) test. The research instruments included a personality questionnaire, a mathematical reasoning test, and interview guidelines. Data analysis was carried out through data reduction, data display, and conclusion drawing. The findings reveal that introverted students tend to demonstrate more thorough, in-depth, and systematic reasoning when solving problems. They are more careful in choosing methods and drawing conclusions. In contrast, extroverted students tend to reason more quickly and directly. They focus more on the final result, present their answers concisely, and are more flexible in selecting problem-solving strategies, although they sometimes pay less attention to process details.